Techniques of Fabrication of Provisional Restoration: An Overview - K. M. Regish; Deeksha Sharma; D. R. Prithviraj (International Journal of Dentistry)
A properly fabricated provisional restoration is important in achieving a successful indirect restoration. The importance of provisional restorations as an integral part of fixed prosthodontic treatment is evident from the abundance of the literature pertaining to their importance regarding margin fidelity, function, occlusion, and esthetics. There are a variety of techniques available to suit the individual needs of the clinician and of the clinical situation, from a single unit to a complete-arch provisional fixed prostheses.